Impact of various cryo-preservation steps on sperm rheotaxis and sperm kinematics in bull - Haitham A. Mofadel; Hassan A. Hussein; Hanan H. Abd-Elhafee; Taymour M. El-Sherry (Scientific Reports)
Abstract Semen cryopreservation is an important tool that has massively contributed to the progression of animal reproduction, especially in cattle. Nonetheless, a large part of the sperm population suffers from cryostress and loses fertility during the process. Although bovine semen cryopreservation is more advanced than any other species, there are still some missing links in the technology knowledge. The aim of the current study was to detect the effect of cryopreservation steps on sperm rheotaxis. Semen samples were collected from sex bulls and analyzed inside a microfluidic platform with CASA after each step of cryopreservation, including control, dilution with yolk citrate, cryoprotectant addition, and cooling or freezing. The results showed that positive rheotaxis % (PR) was not affected during cryopreservation. On the contrary, the sperm kinematics of the positive rheotactic sperm undergo significant changes, as velocity parameters (VCL, VSL, and VAP) were lower in both the cryoprotectant adding and cooling/freezing steps than in the control and yolk citrate dilution steps, while progression parameters (LIN and BCF) were higher in the cryoprotectant and cooling/freezing steps than in the control and yolk citrate dilution steps. Beside these results, an interesting phenomenon of sperm backward positive rheotaxis has been observed. The results of backward sperm rheotaxis samples revealed a significant decrease in PR%, while all sperm kinematics except BCF were significantly higher than normal rheotaxis samples. Based on these results, we conclude that positive rheotactic sperm cells are the elite of the sperm population; however, they still get some sublethal cryodamage, as shown by alterations in sperm kinematics. We also suggest that the sperm-positive rheotaxis mechanism is a mixture of an active and passive process rather than a passive physical one.